Implementasi Penggunaan Dana Desa Dalam Pembangunan Infrastruktur di Desa Ngaban - Laksmi Putri Widyaningtias; Ilmi Usrotin Choiriyah (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2026)
This qualitative descriptive research aims to examine the implementation of the use of Village Funds in infrastructure development in Ngaban Village, Sidoarjo. Data from observations, interviews, and documentation were then analyzed with reference to George C. Edward III's policy implementation theory. Regarding communication, the development planning process was carried out through the Village Development Planning Meeting (Musrenbangdes) involving the community, although information dissemination was not yet equitable. Regarding resources, human resources are sufficient, but budget constraints necessitate phased development. In terms of disposition, implementers demonstrate strong commitment and a sense of responsibility. Regarding bureaucratic structure, task distribution is clearly defined, although it is not yet supported by uniform Standard Operating Procedures (SOPs).